Forms and manifestations of the decline in the use of the Arabic language in the media Audio and video (Journal of the College of Basic Education, 2022)
This research is an attempt to come up with an almost accurate description of the linguistic reality witnessed by many media outlets in the Arab world after the state of the dominance of local dialects and the English language became widespread over the Arabic language, and it became an abhorrent phenomenon that must be studied and seriously considered.In this context, the study is exposed to a set of basic pillars in media practices in Arab satellite channels and radios, which the researcher divided into 7 main sections, as follows:The Arabic language between colloquial and foreign languages ​​in a quick historical overview.- Names and addresses of Arabic stations and radio stations.A new approach to the Arabic language in news programs.- Translation in Arab satellite channels.- Advertising on Arab satellite channels and radios.- Language in the songs of satellite channels and Arabic radio.Findings and recommendations.The researcher discussed the expected problems and their repercussions - especially in the long term - on the possibility of a low level of performance and vulgarity of form and content, and what could cause the acquisition of hybrid vocabulary on mutual understanding and awareness of the recipient, and the possibility of this affecting the youth crowd in particular.The study also deals with the most important methods of hidden and declared linguistic conflicts in Arab media institutions, and the low linguistic competence of their employees, as the crisis that the Arabic language is experiencing today in our media, is a multi-entry crisis, and in many levels, it is no longer possible, but the researcher can go Beyond that, in his understanding of the current linguistic situation, which can undermine cultural creativity and intellectual production, because a hybrid tongue that is alien to the soil of his nation can only be born (a hybrid culture), and (a strange and alienated thought), and even a human alienated and far from his general private environment. Because it loses its identity and originality.